The MADS transcription factor XAL2/AGL14 modulates auxin transport during Arabidopsis root development by regulating PIN expression. (11th October 2013) - Garay‐Arroyo, Adriana; Ortiz‐Moreno, Enrique; de la Paz Sánchez, María; Murphy, Angus S; García‐Ponce, Berenice; Marsch‐Martínez, Nayelli; de Folter, Stefan; Corvera‐Poiré, Adriana; Jaimes‐Miranda, Fabiola; Pacheco‐Escobedo, Mario A; Dubrovsky, Joseph G; Pelaz, Soraya; et al.
<x xml:space="preserve">Abstract</x> Elucidating molecular links between cell‐fate regulatory networks and dynamic patterning modules is a key for understanding development. Auxin is important for plant patterning, particularly in roots, where it establishes positional information for cell‐fate decisions. PIN genes encode plasma membrane proteins that serve as auxin efflux transporters; mutations in members of this gene family exhibit smaller roots with altered root meristems and stem‐cell patterning. Direct regulators of PIN transcription have remained elusive. Here, we establish that a MADS‐box gene (XAANTAL2, XAL2/AGL14) controls auxin transport via PIN transcriptional regulation during Arabidopsis root development; mutations in this gene exhibit altered stem‐cell patterning, root meristem size, and root growth. XAL2 is necessary for normal shootward and rootward auxin transport, as well as for maintaining normal auxin distribution within the root. Furthermore, this MADS‐domain transcription factor upregulates PIN1 and PIN4 by direct binding to regulatory regions and it is required for PIN4‐dependent auxin response. In turn, XAL2 expression is regulated by auxin levels thus establishing a positive feedback loop between auxin levels and PIN regulation that is likely to be important for robust root patterning.